Role of magnetic resonance venogram, diffusion and susceptibility weighted imaging in diagnosis of cerebral venous thrombosis - Shrivastav, Ambuj; Sakalecha, Anil kumar; Hegde, Purnima (International Journal of Research in Medical Sciences, 2016)
Background: Cerebral venous thrombosis (CVT) is an uncommon and sometimes critical disease, especially in untreated patients. CVT is an elusive diagnosis because of its nonspecific presentation and its numerous predisposing causes. Accurate diagnosis is difficult but important because effective therapies, including anticoagulants and intrasinus thrombolysis are available. Patients with cerebral venous thrombosis often make dramatic recoveries after anticoagulation. For this reason, accurate diagnosis is important and critical. The aim was to study the extent of venous sinus involvement and associated cerebral parenchymal changes on magnetic resonance venogram (MRV); to study the pattern of diffusion weighted images and ADC (apparent diffusion coefficient) mapping in patients with cerebral venous thrombosis; to study the role of susceptibility weighted images in patients with cerebral venous thrombosis. Methods: Study was conducted on 34 patients diagnosed to have cerebral venous thrombosis on imaging. Results: Imaging analyses of 34 patients (19 females, 15 males, and age range 19-75 years) were done. Thrombus on MRV was seen as loss of high flow signal from the sinus in cases of complete occlusion of the sinus and frayed or patchy flow signal in the cases of non-occlusive thrombus. 16 patients with hemorrhagic infarct showed heterogeneous signal intensity on DWI (diffusion weighted imaging) and blooming on SWI (suseptibility weighted imaging) sequence. 13 patients with non-hemorrhagic infarct showed multifocal high signal intensities in DWI with variable ADC values and no blooming on SWI. 5 patients with intracerebral hematoma showed areas of heterogeneous signals on DWI with blooming on SWI, corresponding ADC values were variable. Conclusions: MRV, diffusion and susceptibility weighted imaging can be used to evaluate the extent of thrombus, discriminate between different types of edema, detect intracerebral hematoma, hemorrhagic and non-hemorrhagic infarcts, and deliver time-saving information for early diagnosis of CVT.